2011
DOI: 10.1111/j.1365-2893.2011.01462.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing hepatitis B stigma in Chinese immigrants

Abstract: Health-related stigma is a cause of stress, alienation and discrimination that can serve as a barrier to prevention and care for infectious diseases such as HIV. Hepatitis B virus (HBV)-related stigma is common in Asian immigrants, but has not been formally evaluated. The aim of this study was to develop and validate the first HBV stigma instrument and to begin to evaluate HBV stigma in Chinese immigrants. The HBV stigma instrument was developed based on constructs from validated HIV stigma scales and organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
135
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(156 citation statements)
references
References 16 publications
14
135
7
Order By: Relevance
“…24,25 Our study found that 51.81% of participants who received a vaccination were likely to display severe HBV-related discrimination compared to 43.86% that were unimmunized. This result contrasts with other studies, 4,12 where participants who have received HBV vaccination displayed reduced HBV-related discrimination by decreasing their fear of contagion. We speculate that since immunized participants were more aware of the consequences of HBV, they displayed more fear of contagion than unimmunized participants.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…24,25 Our study found that 51.81% of participants who received a vaccination were likely to display severe HBV-related discrimination compared to 43.86% that were unimmunized. This result contrasts with other studies, 4,12 where participants who have received HBV vaccination displayed reduced HBV-related discrimination by decreasing their fear of contagion. We speculate that since immunized participants were more aware of the consequences of HBV, they displayed more fear of contagion than unimmunized participants.…”
Section: Discussioncontrasting
confidence: 55%
“…17 HBV stigma was greatest in the fear of contagion domain. 12 We found that fear of being infected with HBV was significantly associated with rural migrant worker HBV-related discrimination (See Table 4). Most previous qualitative studies showed that discrimination stemmed from lack of knowledge about HBV and the way it is transmitted rather than fear of HBV infection.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Incorrect knowledge about the modes of HBV transmission can lead to misguided preventive behaviors and continued stigma against those with HBV [23]. Concern about social stigma has been a documented barrier to HBV screening, diagnosis, and treatment: respondents face fear and shame regarding transmission of HBV to their loved ones and discrimination in the workplace or school [18,25,27,28]. For example, the high rate of participants incorrectly believing that HBV could be spread by sharing food, drink, or utensils demonstrates the high level of distress regarding the contagiousness of HBV, which can hinder open discussions regarding HBV.…”
Section: Discussionmentioning
confidence: 99%